The crowds in the Gospel of Matthew - Cousland, J. R. C. (Supplements to Novum Testamentum ;, 2002)
This volume identifies the crowds in the Gospel of Matthew and explains their character and function. It argues that a proper appreciation of the crowds is essential to an understanding of salvation history in the gospel.